Cryopreservation of Danube barbel Barbus balcanicus sperm and its effects on sperm subpopulation structure - Kojadinović, Nataša M.; Marinović, Zoran; Veličković, Tijana Z.; Milošković, Aleksandra M.; Jakovljević, Marija M.; Horváth, Ákos; Simić, Vladica M. (Archives of Biological Sciences, 2020)
Paper description: There is no cryopreservation protocol for Danube barbel sperm, although more than 200 species-specific protocols for different freshwater fish species have been developed. The effects of different cryoprotectants and their concentrations, different cooling rates, and the effect of sugar and protein supplementation during development of a successful protocol for cryopreservation of Danube barbel sperm were investigated. The most suitable conditions for cryopreservation were obtained using cryomedium consisting of 5% DMSO supplemented with 0.1 M sugars. The first successful cryopreservation protocol of Danube barbel sperm is essential for the preservation of the unique genetic resources of natural populations. Abstract: The objective of this study was to develop a successful freezing protocol for cryopreservation of Danube barbel sperm, and to identify the presence of different spermatozoa subpopulations. By testing different concentrations of different cryoprotectants, we determined that the use of 5% dimethyl sulfoxide (DMSO) yielded the highest total motility of 25%. Cooling rates influenced by frame height and cooling time in liquid nitrogen vapor showed that a frame height of 3 cm and cooling time of 2 min yielded the highest post-thaw motility. Supplementation of cryomedia with 0.1 M of sugars led to an increase in the total post-thaw motility by 50%, while protein supplementation lowered post-thaw motility. Motile spermatozoa hierarchically clustered according to their motility parameters, displaying a four-subpopulation (SP1-SP4) structure. SP1 was defined by low values of velocity but high overall linearity; SP2 was comprised of fast non-linear spermatozoa, that had high velocity values but low linearity; SP3 was characterized by fast linear spermatozoa, and SP4 by slow non-linear spermatozoa. Protocols developed in this study will lead to the creation of new and enhanced conservation strategies for this species.